Balance between von Willebrand factor and ADAMTS13 following major partial hepatectomy - Groeneveld, D. J.; Alkozai, E. M.; Adelmeijer, J.; Porte, R. J.; Lisman, T. (British journal of surgery, 2016)
Background Conventional coagulation tests are frequently prolonged after liver surgery, suggesting a postoperative bleeding tendency. At the same time, thrombotic complications following partial hepatectomy (PH) are not uncommon. Little is known about changes in the platelet adhesive protein von Willebrand factor (VWF) and its cleaving protease a disintegrin and metalloprotease with a thrombospondin type 1 motif, member 13 (ADAMTS13) following a PH. Methods Plasma samples were collected before and after PH and pylorus‐preserving pancreaticoduodenectomy (PPPD), and from 24 healthy individuals. Plasma levels of VWF and ADAMTS13, VWF activity and VWF‐dependent platelet adhesion were measured, and compared between the groups. Results Median (i.q.r.) VWF levels increased more after PH (17 patients) than following PPPD (10), reaching the highest level on postoperative day (POD) 3 (570 (473–656) versus 354 (305–476) per cent respectively; P = 0·009). VWF levels remained raised on POD 30. A decrease in median (i.q.r.) ADAMTS13 activity was observed for both patient groups, reaching the lowest level on POD 7 (24 (16–32) versus 38 (23–66) per cent for PH and PPPD respectively; P = 0·049), and levels remained significantly reduced at POD 30. VWF activity was significantly higher on day 7 following PH compared with PPPD (median (i.q.r.) 517 (440–742) versus 385 (322–484) per cent respectively; P = 0·009), and remained increased at POD 30. VWF‐dependent platelet adhesion under conditions of flow was increased until POD 30 in patients after PH and PPPD, but was more pronounced in the PH group. Conclusion There are changes in the balance between VWF and ADAMTS13 levels and activity in patients after both PH and PPPD. Changes in the VWF–ADAMTS13 axis were more pronounced and of longer duration after PH than following PPPD. Hyper‐reactive haemostasis?